A framework for cooperative engineering - Gil M. Gonçalves (2005)
This paper discusses a framework for Cooperative Engineering (CE) and its prototype implementation. Cooperative Engineering concerns the application of Concurrent Engineering techniques to the design and development of products and of their manufacturing systems by a network of companies coming together exclusively for that purpose. CE is a common practice in many industries such as automotive, aerospace, shipbuilding, defence, and pharmaceutical. This framework provides a formal model for CE. This is done in the context of distributed hybrid systems (DHS), a modelling and control framework for networked systems introduced recently by the control and computer science communities.